2019
DOI: 10.14202/vetworld.2019.774-777
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the presence of Anaplasma, Ehrlichia, and Babesia spp. in goats (Capra hircus) in Cebu, the Philippines

Abstract: Background: Tick-borne diseases are caused by a wide variety of viruses, pathogens, and diseases. Anaplasma, Ehrlichia, and Babesia spp. are among the most known tick-borne pathogens in Asia. In the Philippines, these pathogens were already reportedly present in dogs and large ruminants, but no study has been reported yet evaluating their presence in goats. Aim: The present study aimed to evaluate the presence of Anaplasma, Ehrlichia, and Babesia spp. in goats in Cebu, the Philippines. Materials and Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In the present study, the blood smear examination also demonstrated the presence of intraerythrocytic dark purple microorganisms appearing as coccoid-and pear-shaped. The coccoid-shaped intraerythrocytic parasites were generally identified as Anaplasma, bacteria belonging to the order Rickettsiales, whereas the pear-shaped microorganisms were generally identified as Babesia, protozoa belonging to the order Piroplasmida [18][19][20][21]. The genus and species of these blood parasites remain unidentified as of now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the blood smear examination also demonstrated the presence of intraerythrocytic dark purple microorganisms appearing as coccoid-and pear-shaped. The coccoid-shaped intraerythrocytic parasites were generally identified as Anaplasma, bacteria belonging to the order Rickettsiales, whereas the pear-shaped microorganisms were generally identified as Babesia, protozoa belonging to the order Piroplasmida [18][19][20][21]. The genus and species of these blood parasites remain unidentified as of now.…”
Section: Discussionmentioning
confidence: 99%
“…Anaplasma and Babesia are the intraerythrocytic parasites that commonly infect mammals throughout the world [18][19][20]. The vectors of these two parasites are generally the blood-sucking arthropods [25,26].…”
Section: Discussionmentioning
confidence: 99%